Individual and Contextual Influences on the Start-up Inclination of Women Academics - Schneider, Kaethe; Saeed, Vbronia (Frontiers in Education, 2022)
Although in recent years there has been an increasing interest in studies of academic entrepreneurship, only a few studies investigating the start-up inclination of women working in academia have been reported. This paper investigates intention formation, person input, and contextual factors as predictors for the start-up inclination of academic women at German universities based on the Social Cognitive Career Theory (SCCT). We employ multinomial logistic regression in a sequential analysis. Our data refers to the sample from the “Institut für Mittelstandsforschung” “IfM” Bonn, Germany. Thus, we conduct a secondary analysis. The sample size considered for academic women is 2,340. Person input shows mixed effects on the start-up inclination. Contextual factors; however, exert a positive impact on having a start-up idea among academic females in Germany. Intention formation has a positive influence on having a concrete and non-concrete start-up idea. Our paper intends to fill the research gap by adding to the available models explaining individual and contextual factors that influence having a start-up idea a SCCT-based model that explains the start-up inclination of women working in academia.